Prevalence of iron deficiency anaemia in patients of cholelithiasis undergoing laparoscopic cholecystectomy - Naik, Santosh; Abuji, Kishore; Dahiya, Divya; Sharma, Prashanth; Das, Reena; Behera, Arunanshu; Kaman, Lileswar (International Surgery Journal, 2022)
Background: Gallstone disease (GSD) is a very common condition worldwide and the key event in the cholesterol stone formation is the supersaturation of bile with cholesterol. The role of trace elements like iron, calcium has been suggested in the pathogenesis of gallstones. Both iron deficiency and GSD are more prevalent in India. With this background, we studied the frequency of iron deficiency anaemia in GSD patients. Methods: This prospective observational study enrolled 150 adult patients undergoing laparoscopic cholecystectomy for symptomatic GSD in a north-Indian tertiary care hospital. Complete hemogram, serum ferritin, iron and unbound iron-binding capacity (TIBC) were performed in all patients. To simplify interpretation, anaemia was defined as Hb <12 gm/dl; iron deficiency was defined as either ferritin value lower than the reference range, or, if the ferritin was within the reference range, reduced % transferrin saturation with normal-or-high TIBC. Results: Anaemia was present in 66% and 77.3% were having iron deficiency; of which 84.5% were females. Iron deficiency with anaemia was present in 85.3%; therefore remaining patients had latent iron deficiency. Serum ferritin was normal or raised in 52 (68.1%) patients with iron deficiency, indicating that it is insensitive as a stand-alone test for iron deficiency. Conclusions: At a public health level, our results may suggest that addressing the problem of endemic iron deficiency may also reduce the possible development of GSD in the community. Thus, pre-operative assessment of iron status appears to be a cautious choice in all patients planned for cholecystectomy as indirectly it will address the problem of anaemia in the population.